1999
DOI: 10.1177/002221949903200607
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Students Classified as LD Who Petitioned for or Fulfilled the College Foreign Language Requirement

Abstract: In this study, we compared the cognitive, academic achievement, and demographic profiles of 46 students from one university who had been classified as learning disabled (LD) and had received permission to substitute courses for the university's foreign language (FL) requirement (petition group) with the profiles of 21 students from the same university who had been classified as LD and had fulfilled the university's FL requirement by passing FL courses (nonpetition group). Results showed no significant differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 35 publications
1
42
0
Order By: Relevance
“…Studies with college L2 learners classified as LD have found that students with IQ-achievement discrepancies did not exhibit more severe L1 learning problems or lower L2 aptitude than either LD or other low-achieving students without IQ-achievement discrepancies (Sparks & Javorsky, 1999;Sparks, Philips, Ganschow, & Javorsky, 1999a;Sparks, Philips, & Javorsky, 2002). Also, college students classified as LD who received course substitutions for the L2 requirement (petition) and LD students who fulfilled the college L2 requirement (non-petition) by passing L2 courses did not exhibit significant differences in L1 cognitive ability, L1 achievement, or college entrance scores (i.e., ACT, SAT) (Sparks, Philips, Ganschow, & Javorsky, 1999b; Sparks, Philips, & Javorsky, 2003a).…”
Section: L2 Learners Classified As Ld and Adhdmentioning
confidence: 99%
“…Studies with college L2 learners classified as LD have found that students with IQ-achievement discrepancies did not exhibit more severe L1 learning problems or lower L2 aptitude than either LD or other low-achieving students without IQ-achievement discrepancies (Sparks & Javorsky, 1999;Sparks, Philips, Ganschow, & Javorsky, 1999a;Sparks, Philips, & Javorsky, 2002). Also, college students classified as LD who received course substitutions for the L2 requirement (petition) and LD students who fulfilled the college L2 requirement (non-petition) by passing L2 courses did not exhibit significant differences in L1 cognitive ability, L1 achievement, or college entrance scores (i.e., ACT, SAT) (Sparks, Philips, Ganschow, & Javorsky, 1999b; Sparks, Philips, & Javorsky, 2003a).…”
Section: L2 Learners Classified As Ld and Adhdmentioning
confidence: 99%
“…In related studies, Sparks and his colleagues compared the cognitive, academic achievement, and demographic profiles of 46 students classified as LD at one university who had been permitted to make course substitutions for the FL requirement (i.e., petition students) with the profiles of 21 students from the same university who had been classified as LD and had fulfilled the university's FL requirement by passing FL courses (i.e., nonpetition students; Sparks, Philips, Ganschow, & Javorsky, 1999b). The results showed no significant differences between the two groups on measures of reading, math, and written language, ACT/SAT scores, and graduating GPA when IQ was used as a covariate; however, both groups' IQ scores were in the above-average range (i.e., Petition group ¼ 79th percentile, Nonpetition group ¼ 87th percentile).…”
Section: Miami Universitymentioning
confidence: 99%
“…(Ideas for consideration in formulating such policies can be found in Freed, 1987;Ganschow et al, 1989;and Philips, Ganschow, & Anderson, 1991. ) Recent findings (Sparks, Philips, Ganschow, & Javorsky, 1998a) have suggested that in terms of test scores on cognitive and achievement measures, there is virtually no difference between students who had difficulties learning an FL and yet pursued and completed the college FL requirement, and those who had difficulties learning an FL and received petitions to substitute the FL requirement. Other findings (Sparks, Philips, Ganschow, & Javorsky, 1998b) have shown that students classified as LD who were permitted to substitute courses for one university's' FL requirement did not display statistically significant differences on cognitive and achievement measures when grouped by level of discrepancy between IQ and achievement (i.e., < 1.0 SD, 1.0 to 1.49 SD, > 1.5 SD) .…”
Section: School Policies For Students With Fl Learning Problemsmentioning
confidence: 99%